2011
DOI: 10.1094/phyto-04-10-0113
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Reducing Effect of Chromolaena odorata Extract on Sheath Blight and Other Rice Diseases

Abstract: Sheath blight caused by Rhizoctonia solani (teleomorph: Thanatephorus cucumeris) is a major cause of crop loss in intensive rice production systems. No economically viable control methods have been developed. We screened aqueous extracts of common herbal plants that could reduce sheath blight lesions and found that foliar spraying and seed soaking application of extracts of either fresh or dried leaves of Chromolaena odorata gave up to 68% reduction in sheath blight lesion lengths under controlled and semi-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…The finding are consistent with data obtained from previous studies (Kummee and Intaraksa, 2008;Plodpai et al, 2013). Khoa et al (2011) reported the diseasereducing effect of Chromolaena odorata extract on sheath blight and other rice diseases. Nguefack et al (2013) found that plant extracts and an essential oil are effective for controlling rice disease, tillering, number of panicles and yield increase.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The finding are consistent with data obtained from previous studies (Kummee and Intaraksa, 2008;Plodpai et al, 2013). Khoa et al (2011) reported the diseasereducing effect of Chromolaena odorata extract on sheath blight and other rice diseases. Nguefack et al (2013) found that plant extracts and an essential oil are effective for controlling rice disease, tillering, number of panicles and yield increase.…”
Section: Resultssupporting
confidence: 93%
“…Clove extract completely inhibited the growth of R. solani, R. oryzae, R. oryzae-sativae and Sclerotium hydrophilum (San-Aye and Matsumoto, 2011). Siam weed extract was found to be effective in reducing severity of blast, brown spot and bacterial leaf blight disease of rice (Khoa et al, 2011). Plant extracts contain metabolites including alkaloids, glucosinolates, indole, phenolics, phenylpropanoids, saponins, stilbenes and terpenoids have been reported to exhibit antifungal properties (Dixon, 2001;Lanzotti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…tabacum, A. vera, A. indica, were found significant to manage rice blast disease in-vitro and in-vivo. The research is also in accordance with Khoa et al, (2011) who observed that foliar spray of aqueous extracts of herbal plants have been found effective in reducing rice blast severity. Results on suppression of Bipolaris oryzae under various concentration of plant extracts were significant.…”
Section: Leaf Extract Of Adhatoda Vasica Andsupporting
confidence: 89%
“…Fractionation of Chromolaena odorata extract Cultivation of C. odorata and harvest of leaves took place as described by Khoa et al (2011). The initial extraction of the bioactive compounds was carried out in methanol and water.…”
Section: Methodsmentioning
confidence: 99%
“…Tests of aqueous extracts of wild plants from Vietnam for their ability to control sheath blight revealed that an extract from Chromolaena odorata (Siam weed) reduced disease severity significantly (Khoa 2010;Khoa et al 2011). The C. odorata extract could also control other important pathogens of rice like Bipolaris oryzae, Pyricularia oryzae and Xanthomonas oryzae pv oryzae.…”
mentioning
confidence: 99%